PENGGUNAAN TEKNIK MAKEUP GAYA KOREA PADA TATA RIAS WAJAH GERIATRI - Chelsea Hexa Widiasmara; Nia Kusstianti; Sri Dwiyanti; M.A. Hanny Ferry Fernanda (Jurnal Tata Rias, 2026)
This study aimed to determine the outcomes of geriatric makeup using Korean-style makeup techniques and the quality of the makeup results in terms of wrinkle concealment. This study uses a quantitative descriptive method with a one-shot case study design. The subject of the study was a geriatric woman aged over 45 years with facial skin conditions showing signs of aging. Data collection techniques were peformed trought the application of observation and assessment by three observers who have competence in the field of Makeup Artist experts. Data analysis was carried out using quantitative descriptive analysis by calculating the average value and percentage of the observer's assessment results. The results showed that the use of Korean-style makeup in geriatric makeup obtained a total score of 173 out of a maximum score of 216 with a percentage of 80.1% which is included in the good category. Meanwhile, the quality of the makeup results obtained a total score of 49 out of a maximum score of 60 with a percentage of 81.6% which is included in the very good category. Korean-style makeup techniques can disguise wrinkles and signs of aging, resulting in smoother-looking skin texture and a natural complexion, while also creating a fresher, more youthful appearance. Therefore, it can be concluded that Korean-style makeup can be effectively applied to geriatric makeup, creating a natural, elegant look that suits the characteristics of older skin.